2023
DOI: 10.1111/sms.14440
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in the physical fitness of Brazilian youth: Evidence that fitness is declining for the majority but not for a fit minority

Abstract: BackgroundThere has been a decline in children's physical fitness in recent decades. Such concerns are largely based on evidence from North America, Europe, and Asia. The current study describes the secular trend and variation (spread) in the physical fitness scores of young Brazilians from 2005 to 2022.MethodsThis study is a repeated, cross‐sectional surveillance study (1999–2022). Children and adolescents (n = 65 139; boys = 36 539) participated between 2005 and 2022. In each cohort six physical fitness test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…43,58 Irrespective of weight status, several recent systematic reviews provided an update on general trends in relative muscle strength and handgrip strength and showed a general increasing trend, 23,59 either small negative quadratic trend or stability in muscle power proxies and for speed a small-to-medium increase in recent years no differences between sexes. 23,27,59 Some more recent individual studies showed declines such as the study among Brazilian youth in almost all tests related to MF 37 and adolescents from the United Kingdom. 30 We found an interesting trend in body core strength (i.e., the number of situps in 60s) which increased on average, certainly presenting a challenge in terms of explaining the background of these findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…43,58 Irrespective of weight status, several recent systematic reviews provided an update on general trends in relative muscle strength and handgrip strength and showed a general increasing trend, 23,59 either small negative quadratic trend or stability in muscle power proxies and for speed a small-to-medium increase in recent years no differences between sexes. 23,27,59 Some more recent individual studies showed declines such as the study among Brazilian youth in almost all tests related to MF 37 and adolescents from the United Kingdom. 30 We found an interesting trend in body core strength (i.e., the number of situps in 60s) which increased on average, certainly presenting a challenge in terms of explaining the background of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…28 That said, fitness trends of children and adolescents from only several high-income countries were reported recently. [27][28][29][30]36,37 Fitness levels, similar to adiposity, can vary significantly across countries and even regions from the same country based on socioeconomic development, so it's important to consider each location's specificities. 36,37 Children and adolescents with lower SES have regularly presented less favourable trends in fitness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this, it can be concluded that slightly more than 4 h of physical activity per day, including some moderate‐to‐vigorous intensity activity too, is good goal for children to ensure that their normal growth and maturation as well as fitness develop well in youth. This is important for counteracting worrying global trends in physical (in)activity and fitness in young people 21,22 . It is not forbidden for adults either to try to accumulate as much as possible daily physical activity, in one way or another, to maintain or even increase physical fitness still in adulthood and aging.…”
mentioning
confidence: 99%
“…This is important for counteracting worrying global trends in physical (in)activity and fitness in young people. 21,22 It is not forbidden for adults either to try to accumulate as much as possible daily physical activity, in one way or another, to maintain or even increase physical fitness still in adulthood and aging.…”
mentioning
confidence: 99%